Determination of the type and serotype strains of bacteria Pasteurella isolated from saigas on the territory Republic of Kazakhstan (Experimental biology, 2015)
This paper presents the results of ribotyping and serotyping of strains Pasteurella/Saigas/2010/ZKO/ KZ and Pasteurella/Saigas/2011/ZKO/KZ, isolated from dead saiga in 2010 – 2011 on the territory of the Republic of Kazakhstan by PCR (polymerase chain reaction). With this kind of analysis is defined subtype and serotype of bacteria of the genus Pasteurella. The results of ribotyping and phylogenetic analysis of 16S gene showed that the studied Kazakhstan strains belong to the bacteria of genus Pasteurella, to multocida and subtype multocida. Also, these comparative analyzes of studied strains between themselves showed a 100 % identity. Serotyping method using the Capsule -specific primers for capA, capB, capD, capE and capF is found that the strains Pasteurella/Saigas/2010/ZKO/KZ and Pasteurella/Saigas/2011/ ZKO/KZ are belongs to the serotype B.
Keywords: saiga; Pasteurella multocida; PCR (polymerase chain reaction); typing; ribotyping